Infiltrasi Faham Keagamaan Jama’ah Tablig di Pondok Pesantren - Ali Imron; Makhfud (Indonesian Journal of Humanities and Social Sciences, 2021)
The phenomenon of infiltration of religious ideology and the impact of change has attracted the attention of religious scholars. It has happened at the Al Fatah Islamic Boarding School, which intersects with the Tablighi Jama'at. This study uses a constructivist paradigm, a qualitative approach, the nature of descriptive research, data collection techniques with in-depth interviews, documentation. The results of this study reveal that the Tablighi Jamaat is no different from the Ahlus Sunnah wal Jama'ah; the difference is only in the da'wah method used. In addition, the education system at the Al Fatah Islamic Boarding School before the Tablighi Jama'ah was like the majority of other salaf pesantren but underwent many changes after the entry of the Tablighi Jama'ah ideology.